Clinical features of freezing of gait in Parkinson's disease patients. Issue 4 (9th March 2019) - Sawada, Makoto; Wada‐Isoe, Kenji; Hanajima, Ritsuko; Nakashima, Kenji
Abstract: Objective: To clarify the clinical features of freezing of gait (FOG) in Parkinson's disease (PD) patients by classification into two groups: Clinically observed FOG (CFOG) and self‐reported FOG (SFOG). Methods: Two hundred twenty‐nine PD patients were medically examined in an examination room as well as subjected to a New Freezing of Gait Questionnaire (NFOG‐Q) and analysis of nonmotor symptoms including sleep, cognition, depression, and fatigue. Results: The prevalence of CFOG was 17.9%, while 53.7% of the patients without CFOG reported the presence of FOG via the NFOG‐Q. Univariate analysis revealed that CFOG was associated with longer disease duration, motor dysfunction, sleepiness, fatigue, and cognitive dysfunction. These symptoms, excluding akinesia, apathy, rapid eye movement (REM) sleep Behavior Disorder, and cognitive dysfunction, were also associated with SFOG. Multivariate analysis revealed that long PD duration, postural instability, and gait difficulty (PIGD), along with fatigue, were independent factors for SFOG. Conclusions: SFOG and CFOG have many common clinical features. Although the clinical relevance of SFOG remains unclear, careful attention should be paid to related features in clinical practice. Abstract : We report the prevalence of freeing of gait (FOG) in Parkinson's disease patients.FOG was associated with longer disease, PIGD subtype and fatigue.